Influence Of Iron Toxicity On Growth Yield And Plant Composition Of Major Rice Varieties Cultivated In Kerala - Sheela R (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1993)
A study was made to identify rice cultivars tolerant to iron toxicity situation culture using Hoagland solution. Thirty cultivars popular among the Kerala farmers were screened under the toxic level of 500 ppm iron and toxicity symptom displayed was scored on 1 - 9 scale. The varieties included high yielding and local ones. The varieties viz., Asha, Annapoorna, Aruna, Aswathi, Jaya, Jyothi, Karthika, Neeraja, Onam, Ptb – 2, Ptb – 10, Ptb – 20, Pavizham, Sabari and Santhosh exhibited severe toxicity symptoms with high scores, exceeding five. The plant iron content of these varieties at AT stage was found relatively higher than that of the remaining ones. Asha, Jaya and Jyothi were seriously affected with scores more than 8 and was therefore treated as highly susceptible. In varieties Bhagya, Bhadra, Bharathy, IR – 36, Kanakam, Makam, Rasi, Red Triveni, Remya and white Triveni, the intensity of visible symptom was lesser with scores ranging between 3 and 5. The iron content of the varieties was lower than in the susceptible varieties. These varieties were classified as moderately tolerant since they had the capacity to resist iron toxicity to a reasonable extent. Display of the least symptoms of iron toxicity and scoring were noticed in five varieties viz., H4, Mahsuri, Cherady, Kochuvithu and Keerthy. Plant analysis of these varieties at the At stage indicated the least iron content. In view of the comparatively better performance, these varieties were further examind to find out the comparative effect of increased iron levels at 400, 500 and 600 ppm on their growth and yield. The study indicated that, in general, growth and yield attributing characters as well as the yield decreased with progressive increase in iron level. H4 and Mahsuri recorded relatively higher grain and straw yields as compared to Cherady, Kochuvithu and keerthy. In all the varieties, the nitrogen content increased with increase in levels of iron whereas the uptake decreased. Keerthy recorded the highest content of nitrogen while H4 recorded the highest uptake of nitrogen. The content and uptake of P, K, Ca and Mg decreased in all the varieties as the level of iron was progressively increased. H4 and Mahsuri recorded significantly higher content and uptake of these elements in grain and straw while Keerthy recorded the lowest. The content of iron in all the varieties increased with increase in levels of levels of iron in growth medium. Relatively lower content of iron was recorded in the aerial parts of H4, Mahsuri and Cherady compared to other varieties, whereas roots of these varieties had higher iron content. The uptake of iron increased upto 500 ppm level and thereafter decreased in all the varieties. The study revealed that the varieties H4, Mahsuri, Cherady Kochuvithu and keerthy exhibited better performance even with toxic concentrations of iron. Among these varieties H4, Mahsuri and Cherady performed reasonably well and H4 performed better with regard to tolerance to iron toxicity. These varieties contained higher P, K, Ca and Mg and lesser iron as revealed by plant analysis. Better performance can be attributed to their genetic superiority such as better root development, improved root oxidation capacity and higher nutrient absorbing ability.